Implementasi Program Kesehatan dan Keselamatan Kerja (K3) Berbasis Undang-Undang Dasar 1945 di Industri Manufaktur : Studi Kasus PT.Rehau Indonesia - Hazmi, Ray zul; Soesanto, Edy (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The 1945 Constitution has a close relationship with K3 (Occupational Safety and Health) which is the legal basis that regulates protection for workers to avoid the risk of work accidents and work-related diseases. The 1945 Constitution which is related to K3 contains the objectives, scope, rights and obligations, as well as monitoring and law enforcement systems related to K3 in the workplace. This law aims to create a safe and healthy working environment for all workers, as well as regulating the responsibilities of employers in ensuring occupational safety and health in the workplace. Law Number 1 of 1970 concerning Work Safety is one of the legal umbrellas that underlies the K3 system in Indonesia. This law regulates the basic principles and general provisions in implementing K3 in the workplace. Implementation of Safety and K3 at PT Rehau Indonesia includes steps and policies implemented by the company to maintain the safety and health of its workers. This includes risk identification, prevention of work accidents, K3 training, monitoring of working conditions, and compliance with applicable K3 regulations. The implementation of K3 is very important to ensure a safe and healthy work environment, reduce the risk of work-related injuries and illnesses, and increase productivity and well-being. employee. Concrete steps usually taken by companies include K3 audits, developing safe work procedures, using personal protective equipment, and increasing K3 awareness through training and outreach.